Digital Marketing Strategy for Sustainable Performance of MSMEs: Literature Review - Setiawan, Raditya; Prasetyo, Panggah Tuhu; Yuniawan, Ahyar (Research Horizon, 2025)
The development of digitalization has opened up great opportunities for Micro, Small and Medium Enterprises (MSMEs) to improve business performance sustainably through the adoption of digital marketing strategies. The study explores key themes such as influence analysis methods, the role of digital marketing in improving performance, and the challenges MSMEs face in digital adoption. A systematic literature review methodology and thematic analysis of articles indexed in Scopus between 2020 and 2024 are used in this study. Selected studies that focus on the role of digital marketing strategies in improving the sustainable performance of MSMEs. The review followed PRISMA guidelines to ensure a comprehensive and unbiased selection of articles, with thematic analysis used in identifying key factors and trends in digital marketing approach relevant for MSMEs. The results advance our understanding of how digital marketing helps MSME sustainability, particularly in a market that is highly competitive. The study shows that the use of digital marketing, particularly through social media, digital advertising, these results provide practical insights for stakeholders to support the adoption of digital marketing in the MSME sector through policy support, financial assistance and technological training.